Hepatitis B virus reactivation during direct-acting antiviral therapy for hepatitis C: a systematic review and meta-analysis. (March 2018) - Mücke, Marcus M; Backus, Lisa I; Mücke, Victoria T; Coppola, Nicola; Preda, Carmen M; Yeh, Ming-Lun; Tang, Lydia S Y; Belperio, Pamela S; Wilson, Eleanor M; Yu, Ming-Lung; Zeuzem, Stefan; Herrmann, Eva; et al.
Summary: Background: Direct-acting antiviral (DAA) therapy for chronic hepatitis C virus (HCV) infection might pose a risk for hepatitis B virus (HBV) reactivation in patients coinfected with chronic or resolved HBV infection. The need for HBV antiviral prophylaxis during DAA treatment remains controversial. We aimed to analyse the absolute risk of HBV reactivation in patients with active or resolved HBV infection treated with DAAs for HCV infection. Methods: For this systematic review and meta-analysis, we searched PubMed, Ovid MEDLINE, the Cochrane Central Register of Controlled Trials, and Web of Science from Oct 1, 2010, to Sept 30, 2017, to identify studies of patients with chronic or resolved HBV infection at baseline treated with DAAs for chronic HCV infection. Conference proceedings, abstract books, and references from relevant reviews were also examined for potential studies. Two independent researchers extracted data and assessed quality and risk of bias. Data were pooled by use of random-effects models. The primary outcome was HBV reactivation defined by standardised nomenclature. This study is registered with PROSPERO, number CRD42017065882. Findings: We identified 17 observational studies involving 1621 patients with chronic (n=242) or resolved (n=1379) HBV infection treated with different DAAs. The pooled proportion of patients who had HBV reactivation was 24% (95% CI 19–30) in patients with chronic HBV infection and 1·4% (0·8–2·4) in those with resolved HBV infection. In patients with chronic HBV infection, the pooled proportion of patients with HBV-reactivation-related hepatitis was 9% (95% CI 5–16) and the relative risk (RR) of HBV-reactivation-related hepatitis was significantly lower in patients with HBV DNA below the lower limit of quantification at baseline than in those with quantifiable HBV DNA (RR 0·17, 95% CI 0·06–0·50; p=0·0011). Three major clinical events related to HBV reactivation in patients with chronic HBV infection were reported (one patient had liver decompensation and two had liver failure, one of whom required liver transplantation). In patients with resolved HBV infection, no HBV-reactivation-related hepatitis was reported. Interpretation: HBV reactivation occurs frequently in patients with chronic HBV and HCV coinfection receiving DAA therapy but is rare among patients with resolved HBV infection. Use of antiviral prophylaxis might be warranted in patients who test positive for hepatitis B surface antigen (HBsAg), particularly those with quantifiable HBV DNA. Funding: None.